War photographers - Egiazarov, Vakhtang (The International tax journal, 2024)
The importance and impact of the events of the war are most accurately reflected by the photographs taken directly at the epicenter of the events. Behind these photos stand the brave photographers who are recording the current real events at the cost of their lives. They are called war photographers. Their only weapon is a camera, and their duty is to accurately describe and provide accurate information to future generations.